Therapeutic Hypothermia Modulates S100B and Oxidative Stress in Neonatal Hypoxic–Ischemic Encephalopathy: Implications of SDF4 as a Novel Biomarker - Fatih Isleyen; Celil Yilmaz; Ismail Koyuncu (Journal of Paediatrics and Child Health, 2026)
ABSTRACT Aim This study investigated the dynamic profile of stromal cell‐derived factor 4 (SDF4), a hypoxia‐inducible chemokine and S100B, an established astroglial injury marker, in neonates with hypoxic–ischemic encephalopathy (HIE) undergoing therapeutic hypothermia (TH). Its potential as a biomarker was assessed by examining its relationship with baseline severity, clinical trajectories and metabolic recovery. Methods In this prospective cohort study, 33 term neonates with moderate‐to‐severe HIE treated with TH and 20 healthy controls were enrolled. Serum levels of SDF4, S100B, total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI) and thiol–disulphide homeostasis were measured before TH (baseline) and on Day 5 (after rewarming). Effect sizes (Cohen's d ) were calculated for significant results. Results Before TH, HIE infants had significantly higher SDF4, S100B, OSI and disulphide levels and lower native thiol and TAS than controls (all p < 0.01). Following TH, all six biomarkers changed significantly in the anticipated direction across the total cohort (all p ≤ 0.020). In stage‐specific sub‐analysis, post‐TH reductions in SDF4 and S100B were statistically significant only in Stage 2 HIE ( p = 0.013 and p = 0.030, respectively), whereas oxidative stress parameters (OSI, native thiol, TAS) improved significantly in both severity groups. Conclusion SDF4 appears to be a novel biomarker reflecting both HIE severity and the dynamic response to TH. The selective lack of SDF4 and S100B clearance in Stage 3 HIE highlights a more sustained pattern of neuroinflammatory injury, supporting SDF4's potential role in monitoring metabolic recovery and guiding individualised neuroprotective strategies.